DEVELOPMENT OF INTERTEXTUAL BASED LEARNING STRATEGY USING VISUALIZATION MODEL TO IMPROVE SPATIAL ABILITY ON MOLECULAR GEOMETRY CONCEPT - Zulfahmi Zulfahmi; Wiji Wiji; Sri Mulyani (Chimica Didactica Acta, 2021)
This study aims to develop intertextual-based learning strategies using visualization models to improve students' spatial abilities on molecular geometry concepts. In this study using the method of Research and Development (R and D). The research subjects used were 20 high school 10th grade students. In this study the instrument used was in the form of an intertextual-based learning strategy validation sheet with visualization models, 3D visualization software, and spatial ability tests. Spatial ability consists of three indicators to be evaluated, namely spatial relations, spatial orientation, and spatial visualization. The results of intertextual-based learning strategy research with developed visualization models can improve spatial ability. Students can understand molecular geometry from the concept of VSEPR theory and valence bond theory. Results pre-test student on the spatial relations (26.67 percent), spatial orientation (10.10 percent), and spatial visualization (7.41 percent). After being tested intertextual-based learning strategies with visualization models of students' post-test results on the spatial relations (58.33 percent), spatial orientation (50.00 percent), and spatial visualization (27.78 percent).